Medicinal and Aromatic Plants of South America Brazil (Medicinal and Aromatic Plants of the World,, 2018)
This volume in the series deals with the major Medicinal and Aromatic Plants MAPs of South America, providing information on major aspects of this specific group of plants on that continent (botany, traditional usage, chemistry, production/collection practices, trade and utilization). Brazil, in particular, offers an immense amount of biodiversity, including plants with great pharmacological interest and medicinal importance. The Amazon Basin, in northern Brazil has a highly diverse biota and still harbours a variety of unknown and unstudied plant species for medicinal values. Contributions are from internationally recognized professionals, specialists of the Medicinal and Aromatic Plant domain and have been invited mostly from the members of the International Society for Horticultural Science and International Council for Medicinal and Aromatic Plants.